Epilepsy as the Main Clinical Manifestation of Congenital Hypothyroidism: A Rare Case Report - Lailita Dwi Cahyanti; Aslin Nur Ainiyah; Zidnal Mafaz; Ditya Arisanti (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2025)
Background: Congenital hypothyroidism (CH) is defined as a deficiency of thyroid hormones present at birth and is one of the most common causes of intellectual disability. CH shows several manifestations, but it is rarely reported that CH manifests as epilepsy. To our knowledge, this rare manifestation of congenital hypothyroidism has only been reported four times previously. The potential association between CH and epilepsy remains unclear. Case: We reported a rare case of a 1-year-old child who presented to the emergency department with complaints of recurrent seizures. Laboratory results showed increased TSH levels and decreased FT4 levels. Electroencephalography (EEG) results were expected. The patient was diagnosed with epilepsy and congenital hypothyroidism. The patient received stabilization therapy in the ER and was admitted to the PICU for 7 days. During hospitalization and a seven-day evaluation at home, the patient did not experience any further seizures. Discussion: Epilepsy and congenital hypothyroidism can affect each other through three known pathogeneses: mitochondrial dysfunction, oxidative stress, and failure of amino acid regulation in the brain. Long-term use of some anti-epileptic drugs is known to reduce thyroid hormone levels. Conclusion: Thyroid hormones play an essential role in various aspects of epilepsy. Thyroid function screening in patients with epilepsy may be advisable, especially in patients with developmental disorders and relevant symptoms.